ANALISIS PENGARUH DESAIN PRODUK, PERCEIVED VALUE, DAN PROMOSI TERHADAP CITRA MEREK SEPATU NIKE (Studi pada Konsumen Sepatu Nike di Kota Semarang) - Adiputra, Nizam; Magnadi, Rizal Hari (Faculty of Economics and Business Diponegoro University, 2018)
Nike is one of the sports companies operating in Indonesia, this company has a problem of decreasing brand image in 2016-2018 based on survey results from Top Brand Awards. This study aims to analyze the effect of Product Design, Perceived Value, and Promotion on Brand Image of Nike shoes. This study uses three independent variables namely Product Design, Perceived Value, and Promotion and uses one dependent variable, Brand Image.The sample used in this study were 100 Nike shoes consumers in the city of Semarang. Data collection methods used are questionnaires distributed by non-probability sampling techniques with the type of purposive sampling. Data analysis techniques that are used is Path Analysis.Base on the result study, As well as showing that Product Design, Perceived Value, and Promotion have a positive and significant effect on Brand Image. The Adjusted R Square value is 0.805, indicating that 80.5 percent of the variation in Product Design can be explained by the independent variable in the regression equation. While the remaining 19.5 percent can be explained by other variables outside the independent variables in this study.